ANALYSIS OF SERVICE QUALITY AND CUSTOMER PERCEIVED ON SATISFACTION WITH CUSTOMER EXPERIENCE AS AN INTERVENING VARIABLE IN PATIENTS OF HOSPITAL IN MEDAN CITY - Grea, Eunike Al; Arlina Nurbaity Lubis; Endang Sulistya Rini (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The purpose of this study is to determine directly and indirectly the relationship between service quality variables, customer perceived satisfaction through customer experience. The population in this study were all patients at hospitals in Medan City, the number of which could not be known with certainty. The sample withdrawal used is accidental sampling. The research sample was taken using the Zikmund formula so that a sample size of 100 respondents was obtained. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that Service quality directly has a significant effect on customer experience, service quality directly has a significant effect on satisfaction, customer perceived directly has a significant effect on customer experience, customer perceived directly has a significant effect on satisfaction, customer experience directly has a significant effect on satisfaction, service quality indirectly has a significant effect on satisfaction through customer experience, and then customer perceived indirectly has a significant effect on satisfaction through customer experience.